Analyzing Meaning: An Introduction to Semantics and Pragmatics. Volume 1 - Harding, Bailey (USA: Murphy & Moore, 2021)
Semantics refers to the meaning of words in a Language and the meaning within a sentence.
Includes Bibliographic References and Index.
Keywords: Semantics--Pragmatics--Discourse Analysis